2008
DOI: 10.4161/cbt.7.12.6957
|View full text |Cite
|
Sign up to set email alerts
|

High expression of dopamine receptor subtype 2 in a large series of neuroendocrine tumors

Abstract: The present data demonstrate a high expression of D2R in NETs; this finding is of clinical relevance in view of the potential role of dopaminergic drugs in inhibiting secretion and/or cell proliferation in NETs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 23 publications
2
33
0
1
Order By: Relevance
“…These authors did not find a correlation between the presence of D 2 receptors and grading of the tumors or proliferative activity in their samples. 25 This last finding is supposed to be related to the absence of poorly differentiated NETs in their series and it is corroborated by the higher D 2 receptor expression shown in chromogranin A positive tumors. However, these preliminary data should be expanded and molecular studies carried out to better address the pathways involved in the high D 2 expression in NETs.…”
Section: Commentarysupporting
confidence: 56%
See 2 more Smart Citations
“…These authors did not find a correlation between the presence of D 2 receptors and grading of the tumors or proliferative activity in their samples. 25 This last finding is supposed to be related to the absence of poorly differentiated NETs in their series and it is corroborated by the higher D 2 receptor expression shown in chromogranin A positive tumors. However, these preliminary data should be expanded and molecular studies carried out to better address the pathways involved in the high D 2 expression in NETs.…”
Section: Commentarysupporting
confidence: 56%
“…18 In summary, the high expression of D 2 dopamine receptors in NETs, shown by the study of Grossrubatscher et al provides new insights on the pathophysiology of NETs and should prompt molecular studies to better address the pathways involved in the high D 2 immunoexpression found in these tumors. 25 These findings may ultimately prove to be of clinical relevance for improving both treatment and survival of these patients in the future. This will be dependent upon showing that they are connected to the downstream signaling pathways related to the inhibition of proliferation.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…They found a high expression of D 2 receptors among the tumors examined (85%), being bronchial carcinoids, islet cell tumors, and the NET of the duodenum the tumors with the highest receptor protein expression (Grossrubatscher et al 2008). Moreover, they observed that a worse clinical outcome was more frequent among patients with less D 2 immunoreactivity, although they could not find a significant correlation between the presence of D 2 receptors and Ki-67 expression in the tumors.…”
Section: Dr Expression In Endocrine Tumorsmentioning
confidence: 68%
“…Accordingly, D2R knockout mice display a phenotype characterized by chronic hyper-prolactinemia and the hyperplasia of lactotrophs (16,25). Although dopamine must exert its actions by binding to specific membrane receptors on pituitary endocrine cells, previous immunohistochemical studies of normal and tumoral lactotrophs have detected D2R immunoreactivities in the cytoplasm but not in the plasma membrane (18,41,48). This is an inconsistent finding concerning the subcellular localization of D2R-though we sometimes experience such a discrepancy with the immunostaining of membrane-bound receptors.…”
mentioning
confidence: 93%